1993
DOI: 10.1007/bf00166025
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental factors on seasonal changes in bacterial cell volume in two prairie saline lakes

Abstract: Bacterial biovolumes of hypertrophic Humboldt Lake (total dissolved solids = 3.3 g liter(-1); 6 m deep) and oligotrophic Redberry Lake (total dissolved solids = 20.9 g liter(-1); 17 m deep), Saskatchewan, were measured concurrently with a variety of environmental variables to identify the major factors correlated with volume changes. There was no difference (P > 0.05) in mean bacterial volume between Redberry Lake (0.084 ± 0.034 μm(3) SD) and Humboldt Lake (0.083 ± 0.021 μm(3) SD). Statistical analyses suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 23 publications
3
8
1
Order By: Relevance
“…Bacterial numbers were high, ranging from 3.5 to 110×10 6 cells ml −1 with a mean of 26.3×10 6 cells ml −1 (±2.0×10 6 cells ml −1 95% CL) but the peak numbers were not associated with the die‐off of the summer cyanobacterial bloom. Mean bacterial cell volume was 0.083±0.021 μm 3 SD, which was not significantly different from the mean cell volume found in a nearby oligotrophic lake [32]. The data from Humboldt Lake, like those from Lake Rodó, do not support a trend of decreasing cell volume with increasing cell number (cf.…”
Section: The Significance Of Heterotrophic Bacteria In Hypertrophic contrasting
confidence: 62%
“…Bacterial numbers were high, ranging from 3.5 to 110×10 6 cells ml −1 with a mean of 26.3×10 6 cells ml −1 (±2.0×10 6 cells ml −1 95% CL) but the peak numbers were not associated with the die‐off of the summer cyanobacterial bloom. Mean bacterial cell volume was 0.083±0.021 μm 3 SD, which was not significantly different from the mean cell volume found in a nearby oligotrophic lake [32]. The data from Humboldt Lake, like those from Lake Rodó, do not support a trend of decreasing cell volume with increasing cell number (cf.…”
Section: The Significance Of Heterotrophic Bacteria In Hypertrophic contrasting
confidence: 62%
“…Thus, it could be concluded that the mean cell-length of planktonic bacteria in all these five watercourses studied, were controlled largely by environmental variables, which is in agreement with the other studies such as, low land water courses of northeast England [49], in a flooded Sep reservoir of France [26], in the hypertrophic Hamboldt Lake and Oligotrophic Redberry lake in Sasktchewan Canada [44], and in sediments of Botany bay in Sydney, Australia which is fed by two rivers, the Cooks river and the Georges river [31]. Further, the strength of the relationship between the overall mean cell-length of planktonic bacteria and environmental variables in the river Lakshmanatheertha with more correlations suggests that, environmental variables have retained a degree of bottom-up (nutrients) control of variation in bacterioplankton cellsize.…”
Section: Discussionsupporting
confidence: 90%
“…The obvious conclusion is that, though the heterotrophic bacterial mean cell length was similar in all the fi ve watercourses, different sets of environmental variables apparently controlled cell size in the different water bodies studied. Similar observations were made for the hypertrophic Humboldt lake and oligotrophic Redberry lake in Saskatchewan, Canada (Tumber et al 1993), in a recently fl ooded oligomesotrophic reservoir in France (Jugnia et al 2000) and in sediments of Botany Bay in Sydney, Australia, which is fed by two rivers-the Cooks and the Georges rivers (Lee and Patterson 2002).…”
Section: Discussionsupporting
confidence: 65%